Secondary Thrombocytosis as a poor prognostic indicator in ovarian carcinoma - Dr. Shwetha Ramu; Dr. SupriyaSandeepa; Dr. Ruchi Sinha; Dr. Narayana Murthy (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Secondary thrombocytosis has been identified in many solid tumors including ovarian carcinoma and has a poor prognostic value in many cases. Platelets and Platelet-related factors may contribute to metastasis, invasion and primary tumor growth.Objective: The objective of the present study is to determine the incidence of thrombocytosis in ovarian carcinoma and its importance as a poor prognosticator.Materials and methods: One sixty cases of epithelial ovarian tumors were studied prospectively between the period of October 2010 to June 2012 in the Department of Pathology, Kasturba Medical College Mangalore. Other causes of secondary thrombocytosis were excluded from the study. All the data for all the cases were obtained and were statistically analysed by Chi-square test and Fisher’s exact test.Results: One sixty cases were studied in the present study. Mean age in the present study was 43.64 years and the mean age of patients with malignancy was 53.18 years. Majority of the cases were benign (64.3%), followed by malignant (31.3%) and borderline tumors (4.4%). Mean platelet count in the study was 321x109 /L, and 80% of malignant cases had thrombocytosis as compared to 42.9% of borderline cases and 5.8% of benign cases, which is highly significant (p=0.0001).Predominant cases of ovarian carcinomas were in stage III (80%) followed by stage IV (17.5%) and stage II (2.5%).Conclusion: Pre-operative secondary thrombocytosis is a frequent finding in ovarian carcinoma and is significantly associated withadvanced FIGO stage. The presence of thrombocytosis acts as a poor prognosticator in epithelial ovarian carcinoma.